Factores limitantes de la ejecución presupuestal en inversión de la Municipalidad Distrital de Moche, período 2007 - 2015. - Alva Guzmán, Connie Andrea (2016)
The problem raised in this research is: What factors have limited investment budget execution in the District Municipality of Moche in the period 2007-2015?, to solve the unknown factor have set the following objectives: Evaluate the evolution of the budget allocated for investment in the District Municipality of Moche period 2007-2015; Analyze the investment budget execution in the District Municipality of Moche period 2007-2015; Describe the administrative processes of the Moche District Municipality to carry out investment (pre-investment and investment) identifying the main weaknesses (internal or consulting); Analyze human resources belonging to the areas involved in the investment process and identify deficiencies; Propose policy guidelines to improve implementation of the budget spending on investment of the District Municipality of Moche. The methods used in this study are: The historical method, analytic-synthetic method and inductive-deductive method. the following techniques and Instruments for data collection is used: The documentary technique (information records and documents of the municipality and virtual data) and field technique (questionnaire to officials involved in the investment process). It is concluded that the factors limiting budget execution were: Deficiencies in administrative processes (Inefficient budget planning, lack of coordination between formulator and evaluator, weak monitoring profiles and records made by consulting, no control in compliance with the execution and inefficiency in recruiting the contracting companies). The shortage of staff and specialist consultants for project development / records (A single formulator with little job tenure, coupled with the low frequency of staff training).